ANALISIS EKUITAS MEREK BERBASIS PELANGGAN PADA MINIMARKET INDOMARET DI SALATIGA - Ariyadi, Dody; Putra, Yanuar Surya (AMONG MAKARTI, 2015)
AbstractRetail Business is of the biggest inustry in Indonesia and already seemed to be a broad people's lifestyles. Indomaret is one of  a retail franchise network in Indonesia. Consumer shopping behavior is formed because the value of a brand that increases a sense of pride. The purpose of this study was to examine the analysis of brand equity based customers for Indomaret, conducted to determine the level of Brand Salience, Brand Performance, Brand Imagery, Brand judgments, Brand Feelings and Brand Resonance of Indomaret, so the company can find a clear overview of Indomaret brand in the public eye, especially customers. The number of samples in this study were 200 samples, which ever shopped at Indomaret in Salatiga. The analysis tool used is the chi-square.Overall consumers know the brand equity of  Indomaret seen from the chi-square test salience 2268.244, 1515.336 performance, imagery 1918.372, 5245.927 judgments, feelings 3368.959, 1660.247 and its resonance with the values 232.912 χ²tabel so Ha is significant and responded positively. It can be concluded that the respondents already know, learn, see, feel, and has experience with a mini Indomaret all the time, so that the company already provides for the obligations and assets owned by a brand.      .Keywords:      Ekuitas merek, Brand Salience, Brand Performance, Brand Imagery,Brand Judgments,Brand Feelings, Brand Resonance